2002
DOI: 10.1182/blood.v99.7.2562
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of potential N-glycosylation sites in the immunoglobulin variable region by somatic mutation is a distinctive feature of follicular lymphoma

Abstract: Further understanding of the nature of the cell of origin in FL has been provided by analysis of the immunoglobulin variableregion gene sequences of the tumor cells. During differentiation, normal B lymphocytes undergo a series of recombinatorial and mutational changes in their immunoglobulin variable-region genes. The V(D)J rearrangements of V H and V L genes occur mainly in the bone marrow, and, after encounter with antigen, the somatic mutation mechanism is activated in centroblasts in the GC. [1][2][3] In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
206
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(225 citation statements)
references
References 58 publications
15
206
2
2
Order By: Relevance
“…1 We further showed that subsets of aggressive B NHL acquire sites 2 in contrast to sequences of myeloma, CLL and normal B cells where this is rare. 1 These data suggest positive selection and a critical role for the introduced glycosylation sites in the pathogenesis of FL.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…1 We further showed that subsets of aggressive B NHL acquire sites 2 in contrast to sequences of myeloma, CLL and normal B cells where this is rare. 1 These data suggest positive selection and a critical role for the introduced glycosylation sites in the pathogenesis of FL.…”
mentioning
confidence: 70%
“…To date, this mutation has not been reported in normal controls, lymphoid disorders or in patients with secondary erythrocytosis. [1][2][3][4][5][6][7][8][9][10] In this study, we have analyzed bone marrow or peripheral blood samples from 349 patients (PV, n ¼ 84; ET, n ¼ 243; IMF, n ¼ 22) referred to our diagnostic service for cytogenetic analysis and/or exclusion of the BCR-ABL fusion from several hospitals in the north of Spain between 1996 and 2005. Our study group thus includes the largest series of ET cases reported to date for JAK2 analysis.…”
Section: Letters To the Editormentioning
confidence: 99%
“…We also investigated mutations in this sequence in previously published sequences as well as our own database and found it often mutated, most frequently at Ser (S), in normal B cells as well as in B-cell lymphoma. 3,7 This region seems to be highly conserved in IGHV4 family germline genes (Online Supplementary Figure S1). Analysis of the protein structure 8 shows that KLS amino acids are located at the protein surface, relatively close to the antigen-binding region at a distance similar to the I antigen-binding AVY hydrophobic patch ( Figure 1B).…”
mentioning
confidence: 99%
“…This phenomenon might imply that the most crucial step in this strategy for producing Id vaccine is the biological stabilization of an Id-secreting hybridoma. This is a problem that, per se, is not easily surmountable when dealing with rescue fusions and might even accelerate the transition towards recombinant technologies [23,24] Finally, at the time of writing it is not clear whether the recent identification of acquired, potential glycosylation sites within the amino acid sequences of tumor-specific immunoglobulins [25][26][27] may have an impact on either idiotypic vaccination as a whole or the choice of the methods by which the Id-containing immunoglobulin is rescued.…”
Section: Discussionmentioning
confidence: 99%